Probing the Fermi surface by positron annihilation and Compton scattering: Электронная структура и Ферми поверхность - Dugdale, S.B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Positron annihilation and Compton scattering are important probes of the Fermi surface. Relying on conservation of energy and momentum, being bulk sensitive and not limited by short electronic mean-free-paths, they can provide unique information in circumstances when other methods fail. Using a variety of examples, their contribution to knowledge about the electronic structure of a wide range of materials is demonstrated.